Operating systems demystified - McHoes, Ann McIver; Ballew, Joli (New York : McGraw Hill Education, 2012)
Find out how operating systems work, including Windows, Mac OS X, and Linux. Operating Systems Demystified describes the features common to most of today's popular operating systems and how they handle complex tasks. Written in a step-by-step format, this practical guide begins with an overview of what operating systems are and how they are designed. The book then offers in-depth coverage of the boot process; CPU management; deadlocks; memory, disk, and file management; network operating systems; and the essentials of system security. Detailed examples and concise explanations make it easy to understand even the technical material, and end-of-chapter quizzes and a final exam help reinforce key concepts.
Quick overview -- Understanding boot processes -- Process and thread management -- CPU management -- CPU scheduling and deadlocks -- Managing main memory -- Virtual memory management -- Managing system devices -- File system management -- Introduction to networking -- Routing strategies and conflict resolution -- System protection and security.
Includes index.
Keywords: OPERATING SYSTEMS (COMPUTERS)